A STUDY ESTABLISHING THE IMPORTANCE OF BODY COMPOSITION ANALYSIS, REGULAR PHYSIOTHERAPY AND DIETARY MODIFICATIONS FOR INDEPENDENT AND HEALTHY LIVING AMONG GERIATRIC POPULATION: A DETAILED SYSTEMATIC REVIEW ARTICLE (International Journal of Physiotherapy, 2015)
Background: This systematic review article aims towards comprehensive and elaborative collection of research articles related to the importance of body composition analysis, Physiotherapy and nutrition for independent geriatric lifestyle. The review article includes articles which suggest the importance of Body composition analysis, Physiotherapy interventions, specific exercises and a combination of fat free, fiber, fruit and fluid diet.Methods: A comprehensive electronic search was conducted using electronic databases Pub Med, MEDLINE, Google Scholar, Science Direct, Research gate, ICMJE, DOAJ, DRJI, IOSR, WAME and many others. In Total 3714, Research papers were reviewed which reported, Age ≥50 years, changes in Body composition in elderly , effects of Diet &Exercises on Body composition and effects of regular Physiotherapy in Geriatric health and obesity. Literature search was restricted to the studies conducted during 1980-2015.Results: Finally 55 papers along with references in research proposal were included. Review shows that ageing, body composition, Physiotherapeutic intervention and nutrition play an interdependent role in providing independent and healthy living among geriatric population.Conclusion: Combined and comprehensive interventions in form of periodic Body Composition Analysis, Physiotherapy interventions with Exercise therapy sessions and Nutritional Supplementation, will be more effective in combating ageing and independent healthy living among Geriatric population. Finally with this review we shall conclude that achieving perfect geriatric health depends upon awareness among the geriatric community to periodically analyze their body composition and regularly comply with exercise therapy sessions, subjective Physiotherapy modality sessions and nutritional supplementation. These principles help in achieving physically fit, healthy, happy and independent geriatric Community.